A CLINICAL STUDY OF DRAKSHA GRITHA IN THE MANAGEMENT OF ANAEMIA IN PREGNANCY (GARBHINI PANDU) (AYUSHDHARA, 2020)
A woman requires more nutrition during pregnancy, which is a physiological condition. When compared to non-pregnant women, a pregnant woman needs 2-3 times the amount of iron than usual. Pandu means pallor of body which can be correlated with 'Anemia' of modern science. Many references in Ayurvedic classics denote that Garbhini Pandu is available.Design: 30 patients of Garbhini Pandu were selected from OPD and IPD of Prasuti Tantra and Stree Roga department from Dr. BRKR GAMC, Hyderabad and were administered 15ml of Drakshaghrita twice daily (morning and evening) on empty stomach orally along with Anupana of Sukoshnadugdha consecutively for 90 days.Results: Statistically highly significant results were seen in Pallor, Glossitis, Bhrama, Hrudrava, Hb% and edema of the lower extremity with p< 0.001.Conclusions: The study showed that Draksha Gritha is effective in the management of Garbhini Pandu.